2008
DOI: 10.1007/s10709-008-9264-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome-b variation in Apis mellifera samples and its association with COI–COII patterns

Abstract: Five Mbo I (Mbo-A, Mbo-M, Mbo-C(1), Mbo-C(2) and Mbo-C(3)) and Hinf I (Hinf-1 to Hinf-5) patterns were observed in Apis mellifera samples after restriction of a 485 bp fragment of the mitochondrial cytochrome-b (cyt-b) gene. Associating the cyt-b Restriction fragment length polymorphism (RFLP) pattern of each sample to its respective previously established COI-COII (Dra I sites) pattern, five restriction patterns (Mbo-C(1), Mbo-C(2), Mbo-C(3), Hinf-1 and Hinf-4) were observed in samples of maternal origin asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Mitochondrial DNA has been widely employed for assessing genetic diversity and structure of honey bee populations in the native and introduced ranges. Among the diverse array of mtDNA genes that have been interrogated using sequence or PCR-RFLP data (Collet et al 2007;Ferreira et al 2009;Pinto et al 2005), the tRNA leu -COX2 intergenic region has been largely preferred with hundreds of haplotypes described so far (Meixner et al 2013). By assembling the mitogenomes of 123 individuals representing seven subspecies, we had an unprecedented opportunity to compare patterns obtained from the nearly complete chromosome with those obtained from individual genes and the popular tRNA leu -COX2 marker.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA has been widely employed for assessing genetic diversity and structure of honey bee populations in the native and introduced ranges. Among the diverse array of mtDNA genes that have been interrogated using sequence or PCR-RFLP data (Collet et al 2007;Ferreira et al 2009;Pinto et al 2005), the tRNA leu -COX2 intergenic region has been largely preferred with hundreds of haplotypes described so far (Meixner et al 2013). By assembling the mitogenomes of 123 individuals representing seven subspecies, we had an unprecedented opportunity to compare patterns obtained from the nearly complete chromosome with those obtained from individual genes and the popular tRNA leu -COX2 marker.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the time since divergence ( t ) from equation d = 2rt , where d is the number of substitutions and r the nucleotide substitution rate per site per year. Substitution rates of insect mitochondrial genes vary substantially (Hewitt 1996; Dowton et al 2009; Ferreira et al 2009; Papadopoulou et al 2010; Pons et al 2010), but those of the genus Myrmica are not known. Thus, we used both the general substitution rate of insects, 1.15% Ma −1 (Brower 1994), and the two substitution rates determined by us above from the expansion estimate, 4% Ma −1 and 5% Ma −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Besides the concerns about the aggressive nature of AHB to humans, it has been recently shown that AHB can outcompete native pollinator species in southern Utah, resulting in the local extinction of the Andrenid bee Perdita meconis (Griswold) (Portman et al, 2017). Honey bees have more than 26 subspecies which have been placed into six evolutionary lineages based primarily on morphometrics and their historical geographic distribution (Ruttner, Utah feral honey bees 1988; Sheppard et al, 1997;Franck et al, 2001;Sheppard & Meixner, 2003;Ferreira et al, 2008;Alburaki et al, 2013). These lineages include the A (African group), M (North and Western Europe), C (Southeastern Europe), O (Near East and Middle East) (Ruttner et al, 1978;Ruttner, 1988;Franck et al, 2007;Kandemir et al, 2006;Ferreira et al, 2008;Shaibi et al, 2009;Rortais et al 2011), Y (Ethiopia) (Franck et al, 2001), and Z (Syria and Lebanon) (Alburaki et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees have more than 26 subspecies which have been placed into six evolutionary lineages based primarily on morphometrics and their historical geographic distribution (Ruttner, Utah feral honey bees 1988; Sheppard et al, 1997;Franck et al, 2001;Sheppard & Meixner, 2003;Ferreira et al, 2008;Alburaki et al, 2013). These lineages include the A (African group), M (North and Western Europe), C (Southeastern Europe), O (Near East and Middle East) (Ruttner et al, 1978;Ruttner, 1988;Franck et al, 2007;Kandemir et al, 2006;Ferreira et al, 2008;Shaibi et al, 2009;Rortais et al 2011), Y (Ethiopia) (Franck et al, 2001), and Z (Syria and Lebanon) (Alburaki et al, 2011). Eight subspecies from four lineages (A, C, M and O) were introduced to the United States (Pellett 1938;Sheppard, 1989aSheppard, , 1989b before the enactment of the 1922 Honey Bee Act which ended all importation of adult honey bees due to the mite, Acarapis woodi (Rennie), which was responsible for the Isle of Wight disease (Phillips, 1923).…”
Section: Introductionmentioning
confidence: 99%